2023
DOI: 10.18632/aging.204819
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of D-gal-induced senile liver injury by Rg3, a signature component of red ginseng

Abstract: To investigate the mechanism by which ginsenoside Rg3 regulates oxidative stress (OS) and inflammation through NF/KB pathway to delay mouse liver injury. This work randomized Balbc mice as four groups: Normal, D-gal, Rg3-L, Rg3-H. Paraffin-embedded liver tissue sections were prepared, later, BAX/BCL-2 protein expression was observed by HE, Sirius red, TUNEL and immunofluorescence to detect apoptotic injury and α-SMA/TGF-β protein expression to detect fibrosis, and liver inflammation-related protein NF-KB was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…These findings align with a previous report indicating that aqueous RG extracts suppressed inflammatory translational markers, augmented autophagy activities, and downregulated mRNA expressions of SASPs in aged mouse models [40]. This is likely attributed to 20(R)-ginsenoside Rg3, a rare ginsenoside abundant in RG, which exerts strong anti-inflammatory and antioxidant capacity against hepatic oxidative stress and apoptosis [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…These findings align with a previous report indicating that aqueous RG extracts suppressed inflammatory translational markers, augmented autophagy activities, and downregulated mRNA expressions of SASPs in aged mouse models [40]. This is likely attributed to 20(R)-ginsenoside Rg3, a rare ginsenoside abundant in RG, which exerts strong anti-inflammatory and antioxidant capacity against hepatic oxidative stress and apoptosis [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that saponins can ameliorate lipid metabolism disorders in the body by modulating the production of SCFAs by the gut microbiota. such as hepatic fibrosis, inflammation, and oxidative stress [79]. This shows that saponins can protect the liver and reduce the damage it receives when external factors affect it.…”
Section: Short-chain Fatty Acidsmentioning
confidence: 98%
“…A study showed that Panax ginseng saponins were able to positively affect ethanol-induced alcoholic fatty liver mice by decreasing hepatic endogenous oxidants (ROS, and MDA), increasing the content of antioxidants (GSH, and SOD), and decreasing the levels of inflammatory factors (IL-6, and TNF-α) in order to reduce the oxidative damage and inflammatory response in the liver induced by ethanol treatment [78]. In addition, ginsenoside Rg1 reduces hepatic reactive oxygen species and pro-inflammatory factors through NF-κB and ameliorates aging-induced hepatic injury such as hepatic fibrosis, inflammation, and oxidative stress [79]. This shows that saponins can protect the liver and reduce the damage it receives when external factors affect it.…”
Section: Protective Effects Of Saponins On the Livermentioning
confidence: 99%